Enhancing the triiodide reduction activity of a perovskite-based electrocatalyst for dye-sensitized solar cells through exsolved silver nanoparticles - Xu, M.; Wang, Wei; Zhong, Yijun; Xu, Xiaomin; Wang, J.; Zhou, W.; Shao, Zongping (ROYAL SOC CHEMISTRY, 2019)
Research on the efficient synthesis and application of nanostructured perovskite oxides is attracting intensive attention nowadays. Herein, a silver (Ag) nanoparticle decorated A-site deficient perovskite is prepared using a facile exsolution method and used as a cathode in dye-sensitized solar cells (DSSCs). The Ag nanoparticle modified (La0.8Sr0.2)0.95MnO3-δ composite (e-LSAM) prepared by the exsolution method displays exceptional activity for the electrocatalytic triiodide (I3-) reduction reaction (IRR) in DSSCs, which is much superior to that of the Ag/perovskite hybrids synthesized by physical mixing and impregnation methods due to the strong interfacial interaction and small Ag particle size. DSSC with this newly developed heteroelectrocatalyst shows a high photovoltaic efficiency of 12.4%, surpassing that of the expensive platinum (Pt)-based control cell (9.93%) with an enhancement factor of 25%, which is among the highest performances of Pt-free cathodes reported to date. Moreover, this new composite cathode shows a much superior IRR durability to Pt, indicating its great potential for replacing Pt. This study paves the way for the rational design of active and durable perovskite electrocatalysts for various energy conversion and storage systems.